Initial perception of high school students for the study of space-time quantization applied to black hole entropyInitial perception of high school students for the study of space-time quantization applied to black hole entropy - Pereira da Silva , Jizreel (International Journal of Scientific World, 2024)
The work presents the initial perception of the students through a diagnostic questionnaire, where the research comprised part of one of the works carried out on the "Study of the quantization of space-time applied to the entropy of black holes" with 23 students of the 3rd year of high school in São Cristóvão, Rio de Janeiro, Brazil. The project is part of several subjects introduced on modern and contemporary physics, as well as frontier research themes, aiming at the student-researcher posture and based on the learning theories of Bruner and Moreira, develop significant learning and receive new information and concepts at an elementary level, conditioning for a critical and reflective posture. The questionnaire was applied, and we raised a discussion and analysis of the students' results to verify the initial level of understanding to introduce a more in-depth study.